n Taksonomiese studie van Pelargonium patulum, P. tomentosum en 'n natuurlike Pelargonium-hibried - Van Wyk, N.(Nicoleen) (Stellenbosch : Stellenbosch University, 2012)
Tesis (M. Sc.) -- Universiteit van Stellenbosch, 1990.